AB0150 Understanding The Role of The IL12/iL35 Balance in Sjögren Syndrome. (15th July 2016) - Fogel, O.; Rivière, E.; Seror, R.; Nocturne, G.; Ly, B.; Boudaoud, S.; Gottenberg, J.-E.; Dubost, J.-J.; Le Guern, V.; Dieudé, P.; Chanson, P.; Nititham, J.; et al.
Abstract : Background: Primary Sjögren Syndrome (pSS) is an autoimmune disease mediated by B-cells as evidenced by the occurrence of non-Hodgkin lymphoma mainly involving salivary glands and increased B-cell activation markers in the serum of pSS patients. A type I interferon response is also observed among some patients. However, some mice models and large genetic studies suggest an alternative/coexisting involvement of the Th1 pathway in the pathophysiology of the disease. In fact, polymorphisms of IL-12A, which encodes for IL-12p35, have been associated with pSS 1 . IL-12p35 subunit is shared by 2 heterodimers, IL-12 and IL-35. Objectives: To confirm the genetic association of IL-12A polymorphism with pSS and to elucidate the involvement of the IL-12/IL-35 balance in pSS through functional studies. Methods: The genetic studies were performed on French pSS from 2 cohorts. Functional studies were performed on sorted monocytes and stimulated ex vivo under inflammatory conditions. Interleukin-12A mRNA, IL-12 and IL-35 proteins were quantified by qRT-PCR for mRNA and by ELISA and multiplex kit respectively for IL-35 and IL-12. Results: We confirmed the association between rs485497 and pSS and found an increased level of IL-12 in sera of pSS patients carrying the risk allele (p=0.016). IL-12 was increased in pSS compared to healthy controls (p=0.0001), especially in patients with a more active disease contrary to IL-35 which was decreased in pSS (p=0.0001). We observed that 99% of patients with high serum levels of IL-35 did not developed lymphoma versus 93% in the group with low IL-35 (p=0.03). Conclusions: Our findings emphasize the involvement of the balance IL-12/IL-35 in the pathogenesis of pSS. Further studies especially on regulatory B-cells and plasma cells as well as in animal models of autoimmune diseases assessing the effect of recombinant IL-35, would help to decipher whether this regulatory cytokine could be of interest for future therapeutic approaches. References: Lessard CJ, Li H, Adrianto I, Ice JA, Rasmussen A, Grundahl KM, et al. Variants at multiple loci implicated in both innate and adaptive immune responses are associated with Sjögren's syndrome. Nat Genet. nov 2013;45(11):1284–92 Acknowledgement: Année recherche ARS Midi-pyrenées Disclosure of Interest: None declared